Modeling Poliovirus Infection Using Human Engineered Neural Tissue Enriched With Motor Neuron Derived From Embryonic Stem Cells - Cosset, Érika; Hibaoui, Youssef; Ilmjärv, Sten; Dietrich, Pierre-Yves; Tapparel, Caroline; Krause, Karl-Heinz (Frontiers in Cell and Developmental Biology, 2021)
Poliomyelitis is caused by poliovirus (PV), a positive strand non-enveloped virus. Since its discovery in the 1950s, several cell culture and molecular methods have been developed to detect and characterize the various strains of PV. Here, we provide an accurate and standardized protocol to differentiate human embryonic stem cells (hESCs) toward engineered neural tissue enriched with motor neurons (MN ENTs). These MN ENTs expressed markers of motor neuron CHAT and Hb-9 as revealed by immunofluorescence staining and quantitative RT-PCR. Interestingly, our results suggest that motor neurons are responsible for the permissiveness of poliovirus within the MN ENTs. Moreover, our study revealed the molecular events occurring upon PV-3 infection in the MN ENTs and highlighted the modulation of a set of genes involved in EGR-EP300 complex. Collectively, we report the development of a reliable in vitro model to investigate the pathophysiology of PV infection, allowing to both design and assess novel therapeutic approaches against PV infection.